Preparation method and application of high-entropy alloy interface modification layer for garnet solid-state lithium battery
By using the high-entropy alloy TiCrCoNiAl as the interface modified layer material in garnet solid-state lithium batteries, the interface contact problem between LLZO and Li and the growth problem of lithium dendrites is solved, and higher ionic conductivity and longer battery life are achieved , while reducing production costs.
Patent Information
- Application Number
- CN202411646048.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
In garnet-based solid lithium batteries, problems such as interface contact between LLZO and Li and growth of lithium dendrites hinder their commercial application, and the preparation process of existing alloy modified layers is complex and costly.
The high-entropy alloy TiCrCoNiAl is used as the interface modification layer material, and it is deposited on the surface of the garnet solid electrolyte sheet by magnetron sputtering technology to construct the interface modification layer of the high-entropy alloy.
Through the interface modification layer of high-entropy alloy, the interface contact between LLZO and Li is significantly improved, the Li+ transmission path and reactive sites are increased, the growth of lithium dendrites is inhibited, the service life of the battery is improved, and the production cost is reduced.
Smart Images

Figure CN119481253A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of garnet solid-state lithium battery design, and in particular to a preparation method and application of a high entropy alloy interface modification layer for a garnet solid-state lithium battery. Background Art
[0002] Compared with traditional liquid lithium batteries, garnet-based solid-state lithium batteries have both high energy density and safety, and are a promising energy storage device. 12 Interfacial problems such as the interfacial contact between (LLZO) and lithium (Li) anode and lithium dendrite growth during alloying / dealloying processes still hinder the commercial application of garnet-based solid-state lithium batteries.
[0003] Although introducing an alloy modification layer into the LLZO / Li interface can improve the LLZO / Li interface problems to a certain extent, most of the alloy modification layers reported so far are single alloy modification layers and the thickness and surface roughness of the modification layer are usually difficult to control. Therefore, its effect on improving the LLZO / Li interface problems is usually limited and single.
[0004] In addition, some of the metal elements involved in the modified layer are expensive and the preparation process of the modified layer is complicated, which has great limitations in practical applications and is difficult to put into large-scale production. Therefore, developing an interface modification layer with a simple preparation process and low cost is of great significance for further improving the interface problems of garnet-based all-solid-state lithium batteries and promoting their practical applications.
[0005] High entropy alloys are a type of single-phase material proposed in recent years. They are obtained by solid solution of five or more metal elements in equal molar ratios or near molar ratios. With the deepening of research, researchers have found that high entropy alloys show unique effects in thermodynamics, kinetics, microstructure and performance, namely high entropy effect, hysteresis diffusion effect, lattice distortion effect and "cocktail" effect. The high entropy effect generated by the increase of constituent elements is sufficient to overcome the formation enthalpy of single-phase compounds and prevent the formation of harmful intermetallic compounds. At the same time, the complex lattice structure will produce obvious lattice distortion, resulting in the generation of a large number of dislocations and defects. In addition, the performance of high entropy alloys is achieved by the synergistic effect of different constituent elements.
[0006] Therefore, high entropy alloy materials show comprehensive properties far exceeding those of single metal materials and traditional alloy materials, and have been widely used in special occasions such as high temperature and high pressure, as well as in the fields of energy and environment. In the field of energy storage, the synergistic effect of multiple elements can give high entropy alloy materials high lithium affinity, thereby increasing the Li + transport paths and reaction active sites, improving its ionic conductivity and enhancing the uniformity of lithium deposition. Summary of the invention
[0007] To solve the above problems, the present invention provides a preparation method and application of a high entropy alloy interface modification layer for a garnet solid-state lithium battery. A lithium solid-state battery is assembled using garnet LLZO as an electrolyte and metallic lithium as a negative electrode. In order to improve the interface problem between LLZO and Li, a high entropy alloy TiCrCoNiAl target is innovatively selected and deposited on the surface of the electrolyte sheet by magnetron sputtering, thereby constructing a high entropy alloy interface modification layer between the LLZO and Li interface.
[0008] To achieve the above object, the present invention provides a method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery, wherein the high entropy alloy TiCrCoNiAl is used as a target material, and the high entropy alloy is deposited on the surface of a garnet solid electrolyte sheet by magnetron sputtering;
[0009] The diameter and thickness of the high entropy alloy TiCrCoNiAl target are 50.8 mm and 3 mm respectively, and the element contents of Ti, Cr, Co, Ni and Al in the target are 20.9 wt%, 22.7 wt%, 25.8 wt%, 25.6 wt% and 5 wt% respectively.
[0010] Preferably, the process parameters of magnetron sputtering are: sputtering gas argon, constant pressure 3×10 -2 mbar, substrate temperature 22 °C, sputtering power 60 W, and sputtering time 60 min.
[0011] Preferably, the method for preparing the garnet solid electrolyte sheet comprises the following steps:
[0012] S1, according to the garnet solid electrolyte sheet Li7La3Z2O 12 The stoichiometric ratio of the elements in the solution was 1. The lithium carbonate, lanthanum trioxide and zirconium dioxide were dispersed in isopropanol solution. The mixture was heated at 200 r·min. -1 Mechanically ball mill at a speed of 1000 until uniformly mixed;
[0013] S2, drying the mixture obtained in step S1 at 120° C. for 12 h, and then pre-sintering at 950° C. for 6 h; mechanically ball-milling the pre-sintered mixture for 17.5 h, drying it, and pressing it into garnet sheets with a diameter of 12 mm;
[0014] S3. After sintering the LLZO sheet obtained in step S2 at 1250° C. for 15 hours, a garnet solid electrolyte sheet with an average particle size of 7 μm is obtained.
[0015] Preferably, in step S1, lithium carbonate is used in excess of 10 wt% to compensate for lithium volatilization during the subsequent high-temperature heating process, and lanthanum trioxide is dried at 900° C. for 10 h before use.
[0016] Preferably, the garnet solid electrolyte sheet obtained in step S3 is polished with sandpaper of 400, 800, 1200, 1500, 2000 and 3000 grit and stored in an Ar2-filled glove box.
[0017] A high entropy alloy modified garnet solid electrolyte sheet prepared by the method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery.
[0018] An application of the high entropy alloy modified garnet solid electrolyte sheet as described above in the preparation of an all-solid-state lithium symmetric battery, the preparation method comprising:
[0019] (1) In a glove box filled with argon atmosphere, a sandwich-stacked lithium sheet, a high entropy alloy-modified garnet solid electrolyte sheet, and a lithium sheet were heated at 300° C. for 30 minutes to make the lithium sheet adhere to the surface of the high entropy alloy-modified garnet solid electrolyte sheet.
[0020] (2) Assemble a spring, a stainless steel disk, and a high entropy alloy-modified garnet solid electrolyte sheet with a lithium sheet attached into a battery and package it.
[0021] The present invention provides a method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery and its application, which has the following beneficial effects:
[0022] (1) The present invention uses high entropy alloy TiCrCoNiAl as a target material to construct a high entropy alloy interface modification layer between LLZO and Li. Compared with the traditional single metal and alloy interface modification layer, the high entropy effect and cocktail effect generated by multiple elements in the high entropy alloy interface modification layer give it better lithium affinity and higher ionic conductivity, thereby improving interface contact and increasing Li + Transport paths and reactive sites, promoting Li + It shows more outstanding effects in terms of uniform deposition, inhibition of lithium dendrite growth and improvement of battery life;
[0023] (2) The magnetron sputtering process used in the present invention to construct the high entropy alloy interface modification layer can easily prepare a nano-scale ultra-thin alloy layer and deposit it uniformly by adjusting process parameters such as sputtering time;
[0024] (3) The elements Ti, Cr, Co, Ni, Al, etc. in the high entropy alloy TiCrCoNiAl used in the present invention are cheap and easy to obtain, and have potential economic benefits that are incomparable to traditional single precious metal and alloy targets.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a schematic diagram of the Li / TiCrCoNiAl@LLZO / Li symmetric battery structure in Example 1;
[0027] Figure 2 The results of scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) tests, where (a) is the cross-sectional SEM image of TiCrCoNiAl@LLZO, and (b) is the EDS surface scan image of TiCrCoNiAl@LLZO;
[0028] Figure 3 The results of electrochemical impedance spectroscopy (EIS) tests, where (a) is the EIS graph of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at room temperature; (b) is the EIS graph of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at room temperature;
[0029] Figure 4 The critical current density (CCD) test results are shown in Figure 1, where (a) is the critical current density (CCD) diagram of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at 60°C; (b) is the critical current density (CCD) of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at 60°C;
[0030] Figure 5 Shown are the results of cycle stability tests, where (a) is the cycle stability diagram of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at 60°C; (b) is the cycle stability diagram of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at 60°C. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0032] Embodiment 1
[0033] (i) Preparing an LLZO garnet solid electrolyte sheet by a solid phase method, comprising the following steps:
[0034] S1, 17.024 g lithium carbonate (Li2CO3), 29.105 g lanthanum trioxide (La2O3) and 14.835 g zirconium dioxide (ZrO2) precursor were dispersed in 120 mL isopropanol solution and heated at 200 r·min. -1 The mixture was mechanically ball milled at a speed of 1000 nm for 17.5 h to achieve uniform mixing.
[0035] Among them, Li2CO3 needs to be in excess of 10wt% to compensate for the volatilization of lithium during the subsequent high-temperature heating process, and La2O3 must be dried at 900℃ for 10h before use.
[0036] S2. The mixture obtained in step S1 was dried at 120° C. for 12 h, and then pre-sintered at 950° C. for 6 h. Then, the pre-sintered powder was mechanically ball-milled for 17.5 h, dried, and pressed into LLZO sheets with a diameter of 12 mm.
[0037] S3, after sintering the LLZO sheet obtained in step S2 at 1250°C for 15h, an LLZO electrolyte sheet with an average particle size of 7 μm was obtained. The obtained LLZO electrolyte sheet was polished with sandpaper of 400, 800, 1200, 1500, 2000 and 3000 grit and stored in an Ar2-filled glove box.
[0038] (II) Preparation of TiCrCoNiAl high entropy alloy interface modification layer
[0039] The TiCrCoNiAl high entropy alloy interface modification layer is prepared by using high entropy alloy TiCrCoNiAl as the target material and depositing it on the surface of the LLZO electrolyte sheet by magnetron sputtering. The electrolyte after the introduction of the high entropy alloy interface modification layer is named TiCrCoNiAl@LLZO.
[0040] The sputtering process parameters are: sputtering gas argon, constant pressure 3×10 -2 mbar, substrate temperature 22 °C, sputtering power 60 W, and sputtering time 60 min.
[0041] The diameter and thickness of the TiCrCoNiAl target are 50.8 mm and 3 mm respectively. The element contents of Ti, Cr, Co, Ni and Al in the target are 20.9 wt%, 22.7 wt%, 25.8 wt%, 25.6 wt% and 5 wt% respectively.
[0042] (III) Preparation of all-solid-state lithium (Li / TiCrCoNiAl@LLZO / Li) symmetric battery
[0043] The high entropy alloy modified garnet solid electrolyte (TiCrCoNiAl@LLZO) was sandwiched between two lithium sheets with a diameter and thickness of 8 mm and 0.5 mm, respectively, to prepare a Li / TiCrCoNiAl@LLZO / Li symmetric battery, which specifically includes the following steps:
[0044] S1. In a glove box filled with argon atmosphere, the lithium sheet, TiCrCoNiAl@LLZO, and lithium sheet stacked in a sandwich shape are first heated at 300°C for 30 minutes to make the lithium sheet adhere to the surface of TiCrCoNiAl@LLZO.
[0045] S2: Assemble the spring, stainless steel disk and electrolyte with lithium foil in a CR2032 button cell and seal it using a hydraulic press with a sealing pressure of 50 kg cm -3 .
[0046] Schematic diagram of Li / TiCrCoNiAl@LLZO / Li symmetric battery structure Figure 1 shown.
[0047] Comparative Example 1
[0048] The Li / LLZO / Li symmetric battery was prepared by replacing the TiCrCoNiAl@LLZO electrolyte with an unmodified garnet solid electrolyte (LLZO). The other process flows were exactly the same as those of the Li / TiCrCoNiAl@LLZO / Li symmetric battery.
[0049] Experimental Testing
[0050] (I) Scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) test. The cross section of the electrolyte sheet after the deposition of the high entropy alloy interface modification layer was tested by scanning electron microscope (SEM, Thermo scientific Verios G4UC) equipped with energy dispersive spectrometer (EDS, Thermo scientific Verios G4UC) to explore the thickness of the modification layer and its elemental composition and distribution. The results are shown in Figure 2 shown.
[0051] Figure 2 (a) is the cross-sectional SEM image of TiCrCoNiAl@LLZO, and (b) is the EDS surface scan image of TiCrCoNiAl@LLZO. It can be seen that the Ti / Cr / Co / Ni / Al elements are evenly distributed in the high entropy interface modification layer and the thickness of the interface modification layer is about 200nm.
[0052] (ii) Electrochemical impedance spectroscopy (EIS) test.
[0053] The assembled battery was placed in the glove box for 12 h and then taken out. The battery was clamped in the order of positive and negative poles. The battery was subjected to EIS test at room temperature using a battery testing system (Solaltron 1470E) with 10 mV AC in the frequency range of 1 MHz to 0.1 Hz.
[0054] like Figure 3 As shown, (a) is the EIS graph of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at room temperature; (b) is the EIS graph of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at room temperature.
[0055] The obtained EIS spectrum can be used to analyze the kinetics of lithium ion transfer during the battery's charge and discharge process and determine its interfacial impedance.
[0056] Therefore, the lithium symmetric battery (Li / TiCrCoNiAl@LLZO / Li) assembled with the modified garnet solid electrolyte of the present invention exhibits a resistance of 41.3Ω·cm 2 The low interfacial impedance is comparable to that of the lithium symmetric battery assembled with unmodified electrolyte (Li / LLZO / Li, 4795.3Ω·cm 2 ), the interface area specific impedance decreased by 116 times. The lithium symmetric battery (Li / TiCrCoNiAl@LLZO / Li) assembled with the modified garnet solid electrolyte of the present invention has lower diffusion impedance and is more conducive to ion migration.
[0057] (iii) Critical current density (CCD) test.
[0058] The assembled battery was taken out after standing in the glove box for 12 hours, and the battery was clamped in the order of positive and negative poles. The solid-state battery was subjected to an electrochemical stripping / plating test for 0.5 hours at a constant temperature of 60°C using a Neware electrochemical testing system (NEWARE CT-4000) with gradually increasing current to evaluate the critical current density (CCD) of the battery.
[0059] like Figure 4As shown, (a) is the critical current density (CCD) diagram of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at 60°C; (b) is the critical current density (CCD) diagram of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at 60°C. It can be seen that the critical current density of the lithium symmetric battery (Li / TiCrCoNiAl@LLZO / Li) assembled with the modified garnet solid electrolyte of the present invention is increased to 2.47 mA cm -2 , indicating that the high entropy alloy interface modification layer has excellent lithium dendrite inhibition ability.
[0060] (IV) Cyclic stability test.
[0061] The assembled battery was placed in the glove box for 12 h and then taken out. The battery was clamped in the order of positive and negative electrodes. The Neware electrochemical test system (NEWARE CT-4000) was used to test 0.1 mA cm at a constant temperature of 60 °C with a fixed plating / stripping interval of 1 h. -2 Long cycle performance of the battery at high current density.
[0062] like Figure 5 As shown, (a) is the cycling stability diagram of the Li / LLZO / Li lithium symmetric battery assembled with the unmodified garnet solid electrolyte LLZO at 60°C; (b) is the cycling stability diagram of the Li / TiCrCoNiAl@LLZO / Li lithium symmetric battery assembled with the high entropy alloy modified garnet solid electrolyte TiCrCoNiAl@LLZO at 60°C.
[0063] It can be seen that the lithium symmetric battery (Li / TiCrCoNiAl@LLZO / Li) assembled with the modified garnet solid electrolyte of the present invention has a high conductivity at 0.1 mA cm -2 It can stably cycle for more than 1600 h at a current density of , showing excellent cycle stability.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery, characterized in that: The high entropy alloy TiCrCoNiAl was used as the target and deposited on the surface of the garnet solid electrolyte sheet by magnetron sputtering; The diameter and thickness of the high entropy alloy TiCrCoNiAl target are 50.8 mm and 3 mm respectively, and the element contents of Ti, Cr, Co, Ni and Al in the target are 20.9 wt%, 22.7 wt%, 25.8 wt%, 25.6 wt% and 5 wt% respectively.
2. The method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery according to claim 1, characterized in that: The process parameters of magnetron sputtering are: sputtering gas argon, constant pressure 3×10 -2 mbar, substrate temperature 22 °C, sputtering power 60 W, and sputtering time 60 min.
3. The method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery according to claim 1, characterized in that: The preparation method of garnet solid electrolyte sheet comprises the following steps: S1, according to the garnet solid electrolyte sheet Li7La3Z2O 12 The stoichiometric ratio of the elements in the solution was 1. The weighed lithium carbonate, lanthanum trioxide and zirconium dioxide were dispersed in an isopropanol solution and the mixture was heated at 200 r·min. -1 Mechanically ball mill at a speed of 1000 until uniformly mixed; S2, drying the mixture obtained in step S1 at 120° C. for 12 h, and then pre-sintering at 950° C. for 6 h; mechanically ball-milling the pre-sintered mixture for 17.5 h, drying it, and pressing it into garnet sheets with a diameter of 12 mm; S3. After sintering the LLZO sheet obtained in step S2 at 1250° C. for 15 hours, a garnet solid electrolyte sheet with an average particle size of 7 μm is obtained.
4. The method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery according to claim 3, characterized in that: In step S1, lithium carbonate is used in excess of 10 wt% to compensate for lithium volatilization during the subsequent high-temperature heating process, and lanthanum trioxide is dried at 900° C. for 10 h before use.
5. The method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery according to claim 3, characterized in that: The garnet solid electrolyte sheet obtained in step S3 was polished with sandpaper of 400, 800, 1200, 1500, 2000 and 3000 grit and stored in an Ar2-filled glove box.
6. A high entropy alloy modified garnet solid electrolyte sheet prepared by the method for preparing a high entropy alloy interface modification layer for a garnet solid-state lithium battery according to any one of claims 1 to 5.
7. A use of the high entropy alloy modified garnet solid electrolyte sheet as claimed in claim 6 in the preparation of an all-solid-state lithium symmetric battery, characterized in that: The preparation method comprises: (1) In a glove box filled with argon atmosphere, a sandwich-stacked lithium sheet, a high entropy alloy-modified garnet solid electrolyte sheet, and a lithium sheet were heated at 300° C. for 30 minutes to make the lithium sheet adhere to the surface of the high entropy alloy-modified garnet solid electrolyte sheet. (2) Assemble a spring, a stainless steel disk, and a high entropy alloy-modified garnet solid electrolyte sheet with a lithium sheet attached into a battery and package it.
Citation Information
Cited By
Preparation method of negative electrode interface layer and solid-state battery
CN121035123A
Preparation method of interface modification layer based on coffee ring effect and solid-state battery
CN121439892A